RELATIONSHIP BETWEEN HAND OSTEOARTHRITIS AND BENIGN JOINT HYPERMOBILITY - Özlem Bölgen Çimen; Selda Bağış; Günşah Şahin; Ali Biçer; Yasemin Yapıcı; Arzu Kanık; Canan Erdoğan (Archives of Rheumatology, 2003)
Hand OA is a common condition mostly affecting postmenopausal women and causing considerable morbidity. The aim of this study was to determine the association between radiological grades, involved joints, hand-grip strength, and pinch strength in hand osteoarthritis and benign joint hypermobility. One hundred-six postmenopausal female patients with hand osteoarthritis and sixty healthy postmenopausal women were included in this study. Patients’ ages, body mass index (BMI), number of Heberden and Bouchard nodules, proximal interphalengeal (PIP), distal interphalengeal (DIP) and carpometacarpal joint (CMC) involvement, pain scales and Beighton scores were recorded. Our results did not reveal any significant correlation between Beighton scores and radiological grades, involvement localizations, hand-grip strength and pinch strength. In conclusion we may say that, our hand osteoarthritis patients did not show any relationship between benign joint hypermobility and hand osteoarthritis. This result may be also due to joint limitation caused by osteoarthritis.